2018
DOI: 10.1111/jace.15819
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of β‐tricalcium phosphate composite ceramic scaffolds based on spheres prepared by extrusion‐spheronization

Abstract: In this study, β‐tricalcium phosphate/phosphate‐based glass (β‐TCP/PG) composite spheres were prepared by an extrusion‐spheronization method featuring high production and fine control of sphere size. Subsequently, fully interconnected β‐TCP composite ceramic sphere‐based (TCCS) scaffolds were fabricated by sintering the randomly packed β‐TCP/PG composite spheres. The results manifested that at least 20% microcrystalline cellulose (MCC) was required to obtain β‐TCP/PG composite spheres in good spherical shape. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
(106 reference statements)
0
6
0
Order By: Relevance
“…In this case, the positions of diffraction peaks for β‐TCP in the TCP‐GPGs patterns shifted to the higher angles, and the shift extent hinged on the Ga amount in the TCP‐GPGs. The ionic substitution can stabilize the phase stability of β‐TCP, and inhibit its reaction with PG in the sintering process; this explained why fewer or no β‐Ca 2 P 2 O 7 phase was shown in the TCP‐GPG2 and TCP‐GPG3, which were involved with the more ionic substitutions as compared with TCP‐GPG1 (Fig. C).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this case, the positions of diffraction peaks for β‐TCP in the TCP‐GPGs patterns shifted to the higher angles, and the shift extent hinged on the Ga amount in the TCP‐GPGs. The ionic substitution can stabilize the phase stability of β‐TCP, and inhibit its reaction with PG in the sintering process; this explained why fewer or no β‐Ca 2 P 2 O 7 phase was shown in the TCP‐GPG2 and TCP‐GPG3, which were involved with the more ionic substitutions as compared with TCP‐GPG1 (Fig. C).…”
Section: Discussionmentioning
confidence: 99%
“…In the sintering process, the phosphorus-rich PG may react with β-TCP, giving rise to β-Ca 2 P 2 O 7 ; moreover, the metal ions of PG partially replace the Ca ions in the β-TCP lattice, leading to lattice distortion. 17,18,[35][36][37] The position of new peak in the patterns of TCP-GPG1 and TCP-GPG2 was overlapped with the strongest peak of β-Ca 2 P 2 O 7 (JCPDS # 09-346). It is inferred that the β-Ca 2 P 2 O 7 phase was produced as sintering TCP-GPG1 and TCP-GPG2 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study using compacted pure β-TCP, which was densified at 1250 °C, reported a final grain size of 4.6 µm and compact material strength of ~75 MPa [ 37 ]. Moreover, β-TCP and phosphate-based glass composite scaffolds (prepared by extrusion spheronization and then sintered at 1100 °C), resulted in both hexagonal and tetragonal grains ranging from 1 to 20 µm in size; compressive strength of 14 MPa was reported for such scaffolds when the total porosity was 48% [ 38 ]. In comparison, by increasing the β-TCP fraction in the ink, and by sintering at 1240 °C, hexagonal grain sizes of 6.3 µm were obtained in the present study (Fig.…”
Section: Discussionmentioning
confidence: 99%